Forecasting the gross domestic product (GDP) of Malaysia - Bopulas, Brenda (Universiti Malaysia Sarawak, 2011)
This study intends to examine the determinant of Gross Domestic Product (GDP) of Malaysia and use them to forecast the GDP of Malaysia. The empirical test that is used in this study includes unit root test, Johansen cointegration test and correlation test.